2021
DOI: 10.1155/2021/6672579
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Metaheuristic Algorithms in Solar Air Heater Optimization: A Review of Recent Trends and Future Prospects

Abstract: A transition to solar energy systems is considered one of the most important alternatives to conventional fossil fuels. Until recently, solar air heaters (SAHs) were among the other solar energy systems that have been widely used in various households and industrial applications. However, the recent literature reveals that efficiencies of SAHs are still low. Some metaheuristic algorithms have been used to enhance the efficiencies of these SAH systems. In the paper, we do not only discuss the techniques used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 221 publications
0
0
0
Order By: Relevance
“…Use of turbulence promotors in conventional air heater have been shown to be very effective in performance augmentation. [9][10][11][12] Application of turbulence promotors in triangular duct can further augment the thermohydraulic performance as shown by Kumar et al 13 where the ribbed triangular duct solar air heater (TSAH), developed a high thermohydraulic performance parameter (THPP) of 1.89 at a flow Reynolds number of 15,000. Square ribs, 14 circular ribs, 15 forward chamfered ribs, 16 and backward chamfered 17 ribs also provide THPP as high as 1.97, 1.44, 2.14, and 2.08, respectively.…”
Section: Performance Enhancement Techniques For Sahmentioning
confidence: 99%
“…Use of turbulence promotors in conventional air heater have been shown to be very effective in performance augmentation. [9][10][11][12] Application of turbulence promotors in triangular duct can further augment the thermohydraulic performance as shown by Kumar et al 13 where the ribbed triangular duct solar air heater (TSAH), developed a high thermohydraulic performance parameter (THPP) of 1.89 at a flow Reynolds number of 15,000. Square ribs, 14 circular ribs, 15 forward chamfered ribs, 16 and backward chamfered 17 ribs also provide THPP as high as 1.97, 1.44, 2.14, and 2.08, respectively.…”
Section: Performance Enhancement Techniques For Sahmentioning
confidence: 99%
“…Conversely, metaheuristic optimization algorithms are simple, robust, flexible, scalable, and easy in execution for solving complex and real-world problems [12][13][14]. Many metaheuristic algorithms, such as PSO, GA, TLBO, ETLBO, and ABC, etc., have been applied in this search area [15]. From the above-cited literature, the following research gaps are identified: a.…”
Section: Introductionmentioning
confidence: 99%